The IGF/IGFBP system in relation to macroscopic bone architecture in pediatric renal transplant patients - Choukair, Daniela; Rüth, Eva-Maria; Blum, Werner F.; Mohan, Subburaman; Weber, Lutz T.; Tönshoff, Burkhard (Pediatric nephrology, 2010)
The post-transplant bone disease of the peripheral skeleton in pediatric renal transplant recipients is characterized by an inadequately thin bone cortex in relation to muscular force. A major hormonal modulator of periosteal growth is the insulin-like growth factor (IGF)/IGF binding protein (IGFBP) system. We therefore hypothesized that the reduced cortical thickness in these patients may be due to functional IGF deficiency.
Online veröffentlicht am 22. Dezember 2009
Gesehen am 09.03.2023